The impact of mobile phone technology on agricultural extension services delivery: evidence from India - Fu, X; Akter, S (Taylor and Francis, 2016)
This study examines the impact of mobile phone enhanced intervention in agricultural extension service delivery in India. Findings show that the amount, quality and speed of service delivery, have improved significantly because of the intervention. There are also benefits in terms of greater knowledge and awareness of new agriculture practice, farmers' aspiration to try new technology in the future and access to credit. The system does not discriminate farmers from disadvantaged and low education backgrounds. Thus, a system of well-used technology, which is assisted by trained village youths can serve as a tool for inclusive development.